TINJAUAN PENGAJUAN KASASI PENUNTUT UMUM TERHADAP PUTUSAN LEPAS DARI SEGALA TUNTUTAN HUKUM PENGADILAN TINGGI SUMATERA UTARA DALAM PERKARA KEHUTANAN (Studi Putusan Mahkamah Agung Nomor ; 237 K/Pid.Sus/2013) - Silalahi, Valenci Prabowo (GEMA, 2015)
This study aims to determine the legal basis prosecutor filed a cassation against the decision free from any lawsuits as well as the juridical basis of the Supreme Court of Justice judgment in deciding the case against the decision free from any litigation with regard to the provisions listed in the Book Of The Law Of Criminal Procedure as well as the facts that occurred in trial.The method used is the doctrinal legal research. Source material used law is the primary legal materials and secondary law, the law of materials analysis techniques using syllogistic method and interpretation by using a pattern of deductive reasoning.Based on the above it can be seen that the legal reasoning public prosecutor in the case number: 237 K / PID.SUS / 2013 has been in accordance with the provisions of Article 253 paragraph (1) letter a from Book Of The Law Of Criminal Procedure. The verdict free from any lawsuits differ from acquittal therefore, the decision free from any lawsuits no correlation with Article 244 from Book Of The Law Of Criminal Procedure.